The Use of Economic and Mathematical Modeling in Assessing the Competitiveness of Tourism Industry Enterprises - S. N. Medvedeva; V. P. Pavlyuk (Статистика и экономика, 2020)
Purpose of research. Tourism is the most important object in the system of modern economic relations. Its main goal is to create an environment conducive to meeting the needs of tourists, which ensure a steady flow of funds. In turn, the economic subsystem solves the problem of creating a competitive tourism industry – the most important determinant of economic growth. Therefore, the study of the competitiveness of the tourism industry market in ensuring sustainable economic growth of the state and increasing the well-being of the population is an extremely relevant direction in a market economy.At the moment, many international, domestic methods are used to assess the level of competitiveness (competitive opportunities). Methodological support for a comprehensive assessment of the competitiveness of tourism industry enterprises based on economic and mathematical models requires further development. An algorithm for assessing regional competitiveness is given on the example of building an econometric model, and testing it for its practical significance.The purpose of our study is to identify the factors affecting the increase in the level of competitiveness of the tourism potential of the Sevastopol region to ensure a sustainable influx of tourists.Materials and methods. The study of the level of increasing competitiveness based on the use of economic and mathematical modeling in the regional aspect is carried out. The «Gretl» software package was used as a statistical tool for the study. The study of the level of competitiveness in the field of the tourism industry in the Sevastopol region is carried out on the basis of a sample of 50 enterprises of the tourism industry, determined by the rating of the volume of gross revenues received per year. To model the share of the gross value added of the tourism industry in the gross regional product at the regional level, we considered the annual financial and economic data of the activities of travel companies, as well as the macroeconomic indicators of the Sevastopol region from 2015-2019. The processing of economic and financial indicators characterizing the micro- and macroeconomics, identification and interpretation of the model is made using computer technologies, in particular the Gretl software package.Results. According to the results of the study, the nature of the relationship between the share of the gross value added of the tourism industry in the gross regional product and the consumer price index, the growth rate of retail turnover, the growth rate of public catering turnover, and the quantity of registered crimes was revealed. Economic and mathematical modeling was carried out using various approaches to constructing the equations of the general model by the least squares method, with fixed or random effects.Conclusion. The article discusses the modeling of competitive advantages in the tourism industry, which makes it possible to determine the significant parameters of independent variables, and it was also proposed that the model with fixed effects is the most adequate for predicting the tourism potential of the Sevastopol region.It should be noted that it is almost impossible to achieve an increase in competitiveness by chance. Therefore, a set of methods and techniques is needed that form an innovative competitiveness management system. The implementation of such a system is directly related to the analysis and assessment of the whole variety of conditions and factors for the functioning of the subjects of the tourism industry.